Human Rights Education in Schools: Contributions from Grassroots Social Organizations - Fernández Fonseca, Edgar (2025)
This article analyzes the key factors that contributed to the development of human rights education, focusing on the role of grassroots social organizations in Bogotá, Colombia, between 1977 and 2007. The study is grounded in documentary and historical research, employing a socio-critical approach. This research addresses the issue of how human rights education in Colombia emerged from the convergence of two social forces that influenced the process of citizenship formation on one hand, the country sought to align its policies with international demands amid the Cold War and the establishment of the international human rights system. On the other, grassroots organizations spearheaded social movements that, in response to the State’s fragility, advanced demands for rights, particularly those related to social participation and access to essential services. The analysis reveals that collective political action, driven by organizational processes, forged new forms of learning and mobilization around rights. These practices encompassed solidarity, urban protest, collective resource management, and the struggle for the right to the city. Popular education served as a platform for promoting and activating judicial mechanisms to demand rights, employing participatory and reflective methodologies that resonated throughout the teaching and learning processes about rights within the school system.